Tantangan Pengelolaan dan Upaya Konservasi Mangrove di Kawasan Belawan Sicanang - Harefa, Meilinda Suriani; Sinurat, Ester; Pandiangan, Errason; Sinaga, Agnes (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The mangrove ecosystem on Sicanang Island, Medan Belawan, is facing heavy pressure due to human activities such as land conversion, waste pollution and the impact of climate change. This research uses observation, interviews and documentation methods to identify the factors causing mangrove degradation as well as conservation efforts carried out by the community. The research results show that land conversion into ponds and settlements causes a decrease in vegetation cover of up to 40% in one decade, which has a direct impact on the decline in marine biota populations. In addition, domestic and industrial waste pollution worsens ecosystem damage. However, the local community has initiated various recovery efforts, such as mangrove rehabilitation, sustainable use of resources, and community-based waste management. Collaboration between communities, government, NGOs and educational institutions is key in strengthening conservation efforts and building a sustainable coastal management system.